Proceedings of the third conference : localization & energy transfer in nonlinear systems : June 17-21 2002, San Lorenzo de El Escorial, Madrid - Vázquez, Luis; MacKay, Robert S., 1956-; Zorzano, María Paz (World Scientific, 2003)
This conference was the third meeting organized in the framework of the European LOCNET project. The main topics discussed by this international research collaboration were localization by nonlinearity and spatial discreteness, and energy transfer (in crystals, biomolecules and Josephson arrays).